Performing for Peace and Social Change in Africa's Great Lakes Region - (:unkn) unknown (My University, 2021)
International aid has influenced and, in part, shaped the artistic sector in Africa's Great Lakes region (DRC, Rwanda, Burundi) since the s, a period marked by numerous conflicts and mass violence. Due to NGOs' programmatic foci, artists performing for social change are increasingly compelled to focus on reconciliation and conflict resolution, generating political awareness and bringing about social change, healing and peacemaking. Through a comparative analysis of European and local productions on the genocide this article asks, how and why does an 'NGO-style theatre' develop a specific audience in the region? How have themes such as mass violence, inter-ethnic conflict and social cohesion become the main concerns of the territory's theatre? How do performances made and/or sponsored by NGOs challenge not only theatre's form, its social stakes and functions, but also the conception of its audience and the relationships between actors and spectators?
Keywords: African Research